2004
DOI: 10.4028/www.scientific.net/amm.1-2.81
|View full text |Cite
|
Sign up to set email alerts
|

Fatigue Life and Residual Strength Analysis of Steel-Composite Joints

Abstract: There are many instances where the use of weight saving composite materials for an entire structure is either; too complex, too expensive or unfeasible. In these circumstances the use of a hybrid structure can incorporate the benefits of traditional construction materials, for example steel, coupled with the advantages of composite materials in weight critical areas. In the present study, an investigation was undertaken into the fatigue life characterisation of a hybrid joint for marine application. In additio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 8 publications
0
2
0
Order By: Relevance
“…For instance, a study by Aim [1983] estimated that a 50-m composite naval ship was 2.4 times less stiff than its steel counterpart. Similarly, an article by Boyd [2004a] states that an all composite ship structure greater than 150 meters is currently unfeasible, and that the application of hybrid composite/metal construction needs to be explored further.…”
Section: Materials Systems and Manufacturing Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…For instance, a study by Aim [1983] estimated that a 50-m composite naval ship was 2.4 times less stiff than its steel counterpart. Similarly, an article by Boyd [2004a] states that an all composite ship structure greater than 150 meters is currently unfeasible, and that the application of hybrid composite/metal construction needs to be explored further.…”
Section: Materials Systems and Manufacturing Methodsmentioning
confidence: 99%
“…They concluded that placement of the steel has a significant effect on the strength and should be moved away from the point of stress concentrations. Boyd et al [2004aBoyd et al [ , 2004b describe an embedded metal joint connecting a composite sandwich panel to a steel deck for a helicopter hangar. In this application, a steel plate was embedded at the end of a tapered composite sandwich section panel made from FRP skins and a balsa core.…”
Section: Connections In Hybrid Structuresmentioning
confidence: 99%